Chronicling Pakistan's Art Movements from Traditional to Contemporary: 1960–2011 - Syed, Kanwal; Abdullah, Sarena (Penerbit Universiti Sains Malaysia, 2015)
The paper discusses modern art in Pakistan by arguing that the artistic discourse in Pakistan has always been in one way or the other influenced by various social and political factors either nationally or internationally. It discusses how the political regimes that preceded each other directed the artistic discourse in the country from which contemporary art works have evolved. This paper divides the Pakistan artistic development into four major phases. The first phase discusses the artists' struggle for identity after independence. The second period shows the censorship in art under General Zia's regime until 1988. The third phase constitutes the 1990s, which can be termed as the transitional period towards contemporary socio-political art and finally the fourth phase reflects the contemporary socio-politically charged imageries in art since 2001. The discussion on the fourth phase will also demonstrate how the role of "contemporary" as a globalised art movement concentrating on regionalism and the Third World, has facilitated the legitimisation of Pakistani artists internationally, who are engaging the political chaos in their country as their artistic concern.